Survey develpoment in the waters around Sabah via a Parangkang Sailing Expedition - Ismail Ali; Mosli Tarsat; Mohammad Raduan Mohd Ariff (Department of Southeast Asian Studies, Faculty of Arts and Social Sciences, University of Malaya, 2010)
Sabah, one of the states of Malaysia in the northern part of Borneo, is surroundedby South China Sea in the west, Sulu Sea in the east, and Celebes Sea in thesoutheast. History has proven that the tides of these three seas played a significantrole in the formation of modern Sabah. Focussing on the importance of maritimeaspect, some sailors from the University of Malaysia in Sabah (UMS) in cooperationwith various agencies made use of traditional boat known as parangkang amongthe Bajaus in navigating the aforementioned seas around Sabah on April 11–May6, 2009. The objective of this expedition was to determine and consider somequestions on maritime Sabah which must be addressed by researchers and otherimportant agencies. Part of the results of this expedition showed that the three seasare not only worthy of its salinity but also as an identity marker of what Sabah isdue to the fact that it is dynamic and always changes just like its tides.